2011
DOI: 10.1371/journal.pone.0026814
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatising Attitudes among People Offered Home-Based HIV Testing and Counselling in Blantyre, Malawi: Construction and Analysis of a Stigma Scale

Abstract: BackgroundHIV/AIDS related stigma is a major barrier to uptake of HIV testing and counselling (HTC). We assessed the extent of stigmatising attitudes expressed by participants offered community-based HTC, and their anticipated stigma from others to assess relationship with HIV test uptake. From these data, we constructed a brief stigma scale for use around the time of HIV testing.Methods and FindingsAdult members of 60 households in urban Blantyre, Malawi, were selected using population-weighted random cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Based on the mean score of each dimension of stigma, our sample of female heads of household expressed moderate-to-low levels of stigma. This endorsement of moderate-to-low intensity of stigma is consistent with findings from recent studies done elsewhere in the Sub-Saharan region [59]. Of the 11 statistically significant correlates, only one variable (HIV transmission route knowledge) has identical effects on both dimensions of stigma.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the mean score of each dimension of stigma, our sample of female heads of household expressed moderate-to-low levels of stigma. This endorsement of moderate-to-low intensity of stigma is consistent with findings from recent studies done elsewhere in the Sub-Saharan region [59]. Of the 11 statistically significant correlates, only one variable (HIV transmission route knowledge) has identical effects on both dimensions of stigma.…”
Section: Discussionsupporting
confidence: 90%
“…[2425262728293031] Our study, however, interestingly found that stigmatization or discrimination toward HIV/AIDs carriers was low. HCPs’ attitudes were characterized by empathy and compassion.…”
Section: Discussionmentioning
confidence: 62%
“…Effective strategies to reduce HIV-related stigma and discrimination are needed to change societal beliefs by increasing the public's HIV-related knowledge, reducing misconceptions about HIV infection and transmission, and correcting inaccurate HIV beliefs. Perhaps high self-perceived HIV risk wrongly manifests itself as an impassioned desire to disclose the status of HIV-positive persons and publically humiliate them, Such motivation by fear of being infected with HIV if one comes into contact with a PLHIV was also reported in a cross-sectional community-based sample survey in Malawi (Macpherson, Webb, & Choko, 2011). Similar attitudes towards those with Tuberculosis were common by community members in the Nicaraguan context (Macq, Solis, Martinez, Martiny, & Dujardin, 2005).…”
Section: Discussionmentioning
confidence: 80%